The influence of psychological capital on academic engagement among Chinese college students - Fan, Xinyuan; Srisawat, Patcharaporn; Voracharoensri, Skol (Journal of Education and Learning (EduLearn), 2026)
The COVID-19 pandemic disrupted education in China, creating uncertainties in students’ academic pursuits. This underscores the urgent need for psychological support to address the ongoing impact on college students. This study delves the relationship between psychological capital and academic engagement among Chinese college students, focusing on four components: efficacy, hope, resilience, and optimism. Through proportional stratified sampling and random selection methods, a sample of 270 students from Liupanshui Normal University were selected. The study employed the positive psychological capital questionnaire (PPQ) and a modified version of Schaufeli’s Utrecht work engagement scale-student to quantitatively measure psychological capital and academic engagement, analyzed via correlation and regression techniques. Results revealed a significant positive correlation between psychological capital and academic engagement. Among the components, hope was the strongest predictor of academic engagement, followed by efficacy as the second most influential factor. Resilience and optimism did not significantly predict academic engagement. These findings highlight the importance of hope and efficacy in enhancing students’ academic involvement, suggesting targeted psychological support could improve engagement. The study contributes to understanding the specific roles of psychological capital components in academic contexts, offering practical insights for educators.